The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/nu15061397
|View full text |Cite
|
Sign up to set email alerts
|

‘Early Introduction’ of Cow’s Milk for Children with IgE-Mediated Cow’s Milk Protein Allergy: A Review of Current and Emerging Approaches for CMPA Management

Abstract: IgE-mediated cow’s milk protein allergy (CMPA) is one of the most prevalent food allergies in early childhood. Though the cornerstone of management involves the strict avoidance of milk products while awaiting natural tolerance, research increasingly shows that the rates of resolution are slowing down. Therefore, there is a need to explore alternative pathways to promote tolerance to cow’s milk in pediatric populations. This review aims to combine and appraise the scientific literature regarding the three CMPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 85 publications
2
15
0
Order By: Relevance
“…In a recent review, the milk ladder was shown to be a safe and effective method of gradual introduction to milk in children with IgE‐mediated CMPA. 4 Two recent studies demonstrated the effectiveness of the iMAP milk ladder in tertiary allergy centres in Ireland and the UK 2 , 5 ; however, the employment of the milk ladder in children with IgE‐mediated CMPA in non‐hospital clinical settings by general practitioners has not yet been evaluated. We reviewed the safety and effectiveness of the use of the milk ladder for children with IgE‐mediated CMPA in a PC setting.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review, the milk ladder was shown to be a safe and effective method of gradual introduction to milk in children with IgE‐mediated CMPA. 4 Two recent studies demonstrated the effectiveness of the iMAP milk ladder in tertiary allergy centres in Ireland and the UK 2 , 5 ; however, the employment of the milk ladder in children with IgE‐mediated CMPA in non‐hospital clinical settings by general practitioners has not yet been evaluated. We reviewed the safety and effectiveness of the use of the milk ladder for children with IgE‐mediated CMPA in a PC setting.…”
Section: Tablementioning
confidence: 99%
“…In a recent review, the milk ladder was shown to be a safe and effective method of gradual introduction to milk in children with IgEmediated CMPA. 4 Two recent studies demonstrated the effectiveness of the iMAP milk ladder in tertiary allergy centres in Ireland and the UK 2,5 ; however, the employment of the milk ladder in children The main outcome was reaching step 12 on the iMAP milk ladder, the introduction of unrestricted liquid cow's milk, which was defined as the uneventful intake of more than 150 mL of cow's milk or the equivalent intake of 4.5 g of milk protein daily. Failure to complete the ladder was defined as the failure to introduce liquid cow's milk after 36 months of follow-up.…”
mentioning
confidence: 99%
“…OIT consists in the daily administration of the maximum tolerated dosage of the offending allergen, previously established through an OFC. After 6–9 months of OIT, another OFC is performed to test the desensitization, while the achievement of tolerance is assessed through an OFC performed after a variable period of the allergen elimination [ 44 ]. OIT apparently involves B-reg and T regulatory cells (Treg), and it leads to a decrease of CMP-specific IgE levels and to an increased level of IgG4 [ 43 , 45 , 46 ].…”
Section: Cow’s Milk Protein Allergy (Cmpa)mentioning
confidence: 99%
“…1 A recent review explored the introduction of baked milk as a treatment for IgE-mediated CMPA and demonstrated that the number of patients who became tolerant to unheated milk during the study periods was greater in the gradual milk introduction group (range 54%-88.1%, mean 62.5%) compared to those who underwent complete avoidance of milk (range 0%-66.7%, mean 21.42%). 2 The aim of this study is to assess the introduction of milk in IgEmediated CMPA using an adapted home introduction milk ladder strategy. All ranges of severity, including those individuals who had anaphylactic reactions, or were already tolerant to baked milk, irrespective of their SPT weal size and specific IgE level were included for analysis.…”
Section: Safety and Effectiveness Of A Milk Ladder For Managing Child...mentioning
confidence: 99%